PENINGKATAN KEMAMPUAN KADER KESEHATAN DALAM PENGELOLAAN DIABETES MELITUS, DI WILAYAH KERJA PUSKESMAS GATAK KABUPATEN SUKOHARJO - Okti Sri Purwanti; Andrian Nur Pratama; Vinda Yulia Dewi (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2016)
Management of diabetes mellitus which is not well can lead to a variety of chronic complications, such as ulcers on the legs, stroke, heart disease, eye, kidney. All the complications can be prevented by increasing the knowledge to manage the DM disease, so that blood sugar levels can be controlled. Increased knowledge can be carried out on persons or health cadres. The purpose of this community service activities is cadre to increase knowledge and skills in the management diabetes mellitus. This writing method with descriptive exploratory, with 20 respondents in total sampling. Activities with counseling on health cadre of 20 people about diabetes mellitus and diabetes nutrition, exercises leg dan examination of blood sugar. The results are increased knowledge of the majority of the 50% pre test enough knowledge, be 70% have a good knowledge, while for gymnastics foot, pre-test post-test exercise less become quite successful foot. Based on the results of blood sugar tests found three people (15%) experienced blood sugar> 200 mg. Suggestions can be submitted, the need for follow-up of the clinic to improve the ability of cadres